Past and Future Explanations for Depersonalization and Derealization Disorder: A Role for Predictive Coding - Gatus, Andrew; Jamieson, Graham; Stevenson, Bruce (Frontiers in Human Neuroscience, 2022)
Depersonalisation (DP) and derealisation (DR) refer to states of dissociation in which one feels a sense of alienation in relation to one’s self and environment respectively. Whilst transient episodes often diminish without treatment, chronic experiences of DP and DR may last for years, with common treatments failing to show reliable symptom reduction. We propose a theoretical explanation of DP and DR based on interoceptive predictive coding, and discuss how transient experiences of DP and DR may be induced in the non-clinical population using virtual reality. Further, we review current methods of detecting the neural correlates of DP and DR using electroencephalography and electrocardiography data, allowing for a better measurement of these experiences in the non-clinical population. Finally, we discuss how the induction and detection of transient experiences of DP and DR in the non-clinical population could shed light on how the brain constructs one's sense of self and reality.